Synthesis and properties of cyclotriphosphazene and perfluoropolyether‐based lubricant with polar functional groups. (18th July 2016) - Wang, Xiaobai; Tan, Angeline Yan Xuan; Cho, Ching Mui; Ye, Qun; He, Chaobin; Ji, Rong; Xie, Hui Qing; Tsai, Jack Wen Huei; Xu, Jianwei
Abstract: A novel hard disk lubricantIDL2 was synthesised by reacting sodium 4‐((2, 2‐dimethyl‐1, 3‐dioxolan‐4‐yl)methoxy)phenoate with hexachlorocyclotriphosphazene, followed by treatment with 1H, 1H‐perfluoro‐3, 6, 9‐trioxatridecan‐1‐ol in the presence of sodium hydride and subsequent hydrolysis using sulfuric acid. The chemical structure ofIDL2 was confirmed by proton nuclear magnetic resonance ( 1 H NMR), phosphorus‐31 ( 31 P) NMR spectroscopy and mass spectrometer. The thermal property ofIDL2 was analysed using thermal gravimetric analysis (TGA) and it shows better thermal stability than two commercial lubricants Z‐DOL and Z‐Tetraol with two and four terminal hydroxy groups, respectively.IDL2 was found to have comparable hydrophobicity to commercial lubricants Z‐DOL, A20H and Z‐Tetraol with water contact angles in the range of 78 – 85°, revealing thatIDL2 has analogous surface energy to these commercial lubricants.IDL2 exhibits comparable friction coefficient to A20H and Z‐Tetraol, but much lower than Z‐DOL. More interestingly, it has a much high bonding ratio when compared with commonly used commercial lubricants under the same testing conditions due to the presence of two polar hydroxy groups, which enhance the interaction between lubricant and substrate. These promising properties ofIDL2 show that it would be very potential for real application as a hard disk drive lubricant. Copyright © 2016 John Wiley & Sons, Ltd.